A specific cognitive behavioral group therapy program for stimulant use disorder - Karsinti, Emily; Vorspan, Florence; Therribout, Norman; Icick, Romain; Bloch, Vanessa; Fortias, Maeva; Piani, Kristel; Romo, Lucia (Frontiers in Psychiatry, 2022)
Introduction Stimulant use is an important health issue. In the US in 2018, 2.8% of males and 1.5% of females older than 18 had used cocaine in the preceding 12 months. Objective To intervene in a specific targeted group of Stimulant Use Disorder (SUD) patients according to CBT and relapse prevention theories, and to determine the program’s feasibility and attendance. Method Stimulant Use Disorder patients in addiction care were evaluated for addictive, psychological and psychiatric dimensions at baseline and conclusion in a 9-session CBT group program with several themes: define SUD, enhance motivation, involve close companions, cope with craving, decline a proposal, solve problems, invite expert patients, invest time and money, and review content. Results In total, 41 patients attended at least one session. They were mainly poly dependent, primarily cocaine users. Sixty percent of the population also suffered from another psychiatric comorbidity. Median attendance for participants was 7/9 sessions. Conclusion A specific targeted CBT group for stimulant dependent highly comorbid patients is feasible. These findings suggest that peers should be included in addiction care services.